#### Answer

$\frac{5}{x^{2}}$

#### Work Step by Step

$\frac{5x-5}{x^{3}-x^{2}}=\frac{5(x-1)}{x^{2}(x-1)}=\frac{5}{x^{2}}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{5}{x^{2}}$

$\frac{5x-5}{x^{3}-x^{2}}=\frac{5(x-1)}{x^{2}(x-1)}=\frac{5}{x^{2}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.